Digital Business and E-Commerce Management: Strategy, Implementation and Practice - Dave Chaffey; David Edmundson-Bird; Tanya Hemphill (United Kingdom Pearson, 2019)
This text offers a comprehensive introduction to the theory and practice of e-business and e-commerce management. The author, Dave Chaffey, brings his trademarks of authority, clarity of expression and teaching expertise to bear on a subject in which he actively lectures and consults. Popular for its cutting-edge and contemporary coverage, this text offers an international approach and a good balance between the technical and managerial topics of central importance to developing an understanding of this subject. Developed for students studying e-business or e-commerce at undergraduate or postgraduate level, and also used by many business managers, this is the essential text to keep pace with technology, strategy and implementation.
Keywords: Electronic commerce; Business enterprises; Computer networks; Business; Marketing; Management; Global Digital Business (BIN2042-N)